HOW TO FIND THE NEXT THREE TERMS IN A SEQUENCE

About "How to Find the Next Three Terms in a Sequence"

How to Find the Next Three Terms in a Sequence :

Here we are going to see some practice questions to find the next three terms in a sequence.

What is Sequence ?

There is some arrangement or pattern followed in every sequence.

There are two types of sequence,

Finite sequence :

If the number of elements in a sequence is finite then it is called a Finite sequence.

Infinite sequence :

If the number of elements in a sequence is infinite then it is called an Infinite sequence.

Question 1 :

Find the next three terms of the following sequence.

(i) 8, 24, 72, …

Solution :

To find the next three, first we have to find out the pattern followed in sequence.

Pattern :

Multiplying the first term by 3, we get the second term.Multiplying the second term by 3, we get the third term.

4th term  =  3 (72)  =  216

5th term  =  216 (3)  =  648

6th term  =  648(3)  =  1944

Hence the next three terms are 216, 648, 1944.

(ii) 5, 1,-3,…

Solution :

Pattern :

By subtracting 4 from the 1st term, we get second term. By subtracting 4 from 2nd term, we get 3rd term.

4th term  =  -3 - 4  =  -7

5th term  =  -7 - 4  =  -11

6th term  =  -11 - 4  =  -15

Hence the next three terms are -7, -11, -15.

(iii) 1/4, 2/9, 3/16,…

Solution :

Pattern :

General term  =  n [1/(n + 1)]2

n is elements of natural numbers.

4th term  =  4 [1/(4 + 1)]2

  =  4[1/5]2

  =  4/25

5th term  =  5 [1/(5 + 1)]2

  =  5[1/6]2

  =  5/36

6th term  =  6 [1/(6 + 1)]2

  =  6[1/7]2

  =  6/49

Hence the next three terms are 4/25, 5/36, 6/49.

How to find next four terms if nth term of the sequence is given ?

Question 1 :

Find the first four terms of the sequences whose nth terms are given by

(i) an = n3 −2

Solution :

To find the 1st term, we have to apply n = 1

an = n3 −2

n = 1

a1 = 13 −2

  =  1 -  2

a1  =  -1

an = n3 −2

n = 2

a2 = 23 −2

  =  8 -  2

a2  =  6

an = n3 −2

n = 3

a3 = 33 −2

  =  27 -  2

a3  =  25

an = n3 −2

n = 4

a4 = 43 −2

  =  64 -  2

a4  =  62

Hence the first four terms are -1, 6, 25, 62.

(ii) an = (−1)n+1 n(n + 1)

Solution :

an = (−1)n+1 n(n + 1)

n = 1

=  (−1)n+1 n(n + 1)

=  (−1)1+1 1(1 + 1)

=  1 (2)

a1  =  2

n = 2

=  (−1)n+1 n(n + 1)

=  (−1)2+1 2(2 + 1)

=  -1 (6)

a2  =  -6

n = 3

=  (−1)n+1 n(n + 1)

=  (−1)3+1 3(3 + 1)

=  1 (12)

a3  =  12

n = 4

=  (−1)n+1 n(n + 1)

=  (−1)4+1 4(4 + 1)

=  -1 (20)

a4  =  -20

Hence the first four terms are 2, -6, 12, -20.

(iii) an = 2n2 - 6

Solution :

an = 2n2 - 6

n = 1

=  2(1)2 - 6

a1  =  -4

an = 2n2 - 6

n = 2

=  2(2)2 - 6

a2  =  2

an = 2n2 - 6

n = 3

=  2(3)2 - 6

a3  =  12

an = 2n2 - 6

n = 4

=  2(4)2 - 6

a4  =  26

Hence the four terms are -4, 2, 12, 26.

After having gone through the stuff given above, we hope that the students would have understood, "How to Find the Next Three Terms in a Sequence". 

Apart from the stuff given in this section "How to Find the Next Three Terms in a Sequence"if you need any other stuff in math, please use our google custom search here.

Widget is loading comments...